PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PERKEMBANGAN PERILAKU PROSOSIAL SISWA - Muniroh, Muniroh (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2019)
This study aims to describe the effect of group guidance services on the development of prosocial behavior of eighth grade students of Junior High School Negeri 17 Medan. The method used is a pseudo-experimental one group pretest-posttest village design. The subjects of this study were 12 students who were selected using purposive sampling techniques. Data collection in this study uses a scale of prosocial behavior. The results of this study indicate the behavior of 12 students increased after being given group guidance services ASYMP. GIG is 0.002, (<0.05) This means that there is a significant influence of group guidance services on the development of prosocial behavior of students of class VIII of Junior High School Negeri 17 Medan.